2021
DOI: 10.1508/cytologia.86.267
|View full text |Cite
|
Sign up to set email alerts
|

Antimitotic and Cytotoxic Effects of Leaf Aqueous Extract of <i>Scadoxus multiflorus</i> (Martyn) Raf. in <i>Allium cepa</i> Root Apical Meristem Cells

Abstract: Scadoxus multiflorus is a traditionally used medicinal plant, widespread in Sub-Saharan Africa from Senegal to South Africa and in some places of Saudi Arabia and India. The present study aimed to analyze antimitotic and cytotoxic effects of leaf aqueous extract of S. multiflorus (LAESM) in Allium cepa root apical meristem cells. The root growth retardation, mitotic index (MI), cytological and mitotic abnormalities were analyzed in A. cepa root apical meristem cells after LAESM treatment. The LAESM induced a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The IC 50 value of LAEMM for RGR was found to be 0.204 mg mL 1 at 48 h. The IC 50 values for the RGR at 48 h are considered reliable for the evaluation of antiproliferative and cytotoxic effects of tested substances (Konuk et al 2007, Barman et al 2020. There are several previous reports available, which showed the antiproliferative and cytotoxic effects of the various plant extracts by analyzing the RGR effects and MAs (Murthy et al 2011, Ray et al 2013, Udo et al 2014, Kundu and Ray 2016, Barman et al 2020, Chakraborty et al 2021, Das et al 2021.…”
Section: Resultsmentioning
confidence: 98%
“…The IC 50 value of LAEMM for RGR was found to be 0.204 mg mL 1 at 48 h. The IC 50 values for the RGR at 48 h are considered reliable for the evaluation of antiproliferative and cytotoxic effects of tested substances (Konuk et al 2007, Barman et al 2020. There are several previous reports available, which showed the antiproliferative and cytotoxic effects of the various plant extracts by analyzing the RGR effects and MAs (Murthy et al 2011, Ray et al 2013, Udo et al 2014, Kundu and Ray 2016, Barman et al 2020, Chakraborty et al 2021, Das et al 2021.…”
Section: Resultsmentioning
confidence: 98%
“…The highest root length retardation percentage (68.51 0.56%, p<0.001) in 150 µg mL 1 at 72 h of AQPEF treatment and IC 50 value of the root growth retardation was 23.68 5.5 µg mL 1 at 48 h treatment (Table 1). Recently, Barman et al (2020) and Das et al (2021) reported that plant extract induced root growth retardation, and the levels of root growth retardation were increased with the increasing extract concentration and suppression of cell division in A. cepa root tips (Murthy et al 2011, Ray et al 2013.…”
Section: Resultsmentioning
confidence: 99%
“…But, the detailed cytotoxic and cytostatic effects of leaf aqueous extract of this plant are not clear. Therefore, we aimed to explore cytotoxic and cytostatic effects of leaf aqueous extracts of C. asiaticum by A. cepa assay, a sensitive and cheap system to measure the cytotoxic effects of pollutants, chemical substances, and plant extracts (Andrade et al 2008, Bakare et al 2012, Frescura et al 2013, Ray et al 2013a, b, Chaudhuri and Ray 2015, Kundu and Ray 2016, Chakraborty et al 2021, Das et al 2021.…”
mentioning
confidence: 99%